Fetal MRI compared with ultrasound for the diagnosis of obstructive genital malformations. (26th October 2017) - Millischer, Anne Elodie; Grevent, David; Rousseau, Véronique; O'Gorman, Neil; Sonigo, Pascale; Bessieres, Bettina; Ville, Yves; Boddaert, Nathalie; Salomon, Laurent J.
Abstract: Objective: To compare the accuracy of magnetic resonance imaging (MRI) and ultrasound (US) to diagnose and characterize congenital obstructive genital abnormalities. Method: Retrospective cohort of 20 fetuses who underwent a fetal MRI following a US diagnosis of obstructive urogenital malformation. We compared MRI and US findings and their correlation with the definitive diagnosis. Result: The correct diagnosis was obtained in 6/20 (30%) cases and 19/20 cases (95%) with US and MRI, respectively. MRI revealed additional information to US in 15/20 cases (75%) and modified the prenatal management in 14 fetuses (70%). The identification rates of the most important anatomical landmarks for the diagnosis, using US and MRI, were compared. Bladder: US 17/20 (85%) vs MRI 20/20 (100%) P  = 0.23; vagina: US 6/19 (31.5%) vs MRI 19/19 (100%) P  < 10 −4 ; uterus: US 11/19 (57.8%) vs MRI 19/19 (100%) P  = 0.003, kidneys: US: 40/40 (100%) MRI: 40/40 (100%) P  = 1, ureters: US 14/40 (35%) vs MRI 30/40 (75%) P =0.001, rectum: US 6/20 (30%) MRI 20/20 (100%) P  < 10 −4, and sacrum: US 20/20 (100%) vs MRI 17/20 (85%) P  = 0.23. Conclusion: In fetuses with obstructive urogenital malformations, MRI facilitates assessment of major pelvic organs and provides significant information that may alter the prenatal management.